Study on the Gravity Processing of Manganese Ores - Malayoglu, U. (Asian Journal of Chemistry, 2010)
Manganese ores from Sindirgi Balikesir region, Kinik district, Turkey are low grade types and need beneficiation to utilize them in ferromanganese and chemical industry. Mineralogical and chemical characterization of ores from this region indicated their susceptibility to manganese enrichment. In this study, the optimum gravity beneficiation method parameters for the production of marketable concentrates from Sindirgi, Balikesir, Turkey manganese ore were investigated. A final concentrate containing 47 % Mn and 20 % SiO2 was produced by the application of the most appropriate beneficiation conditions with ca. 64 % metal recovery. Furthermore, it was found that the concentrates containing 52.62 % Mn, with lower silicate ratio for chemical purposes can also be recovered.